2021
DOI: 10.1109/access.2021.3111287
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Extreme Gradient Boosting Model Integrated With Evolutionary Algorithms for Hourly Water Level Prediction

Abstract: The establishment of reliable water level prediction models is vital for urban flood control and planning. In this paper, we develop hybrid models (GA-XGBoost and DE-XGBoost) that couple two evolutionary models, a genetic algorithm (GA) and a differential evolution (DE) algorithm, with the extreme gradient boosting (XGBoost) model for hourly water level prediction. The Jungrang urban basin located on the Han River, South Korea, was selected as a case study for the proposed models. Hourly rainfall and water lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It’s important to highlight that DE and GA exhibited strongly non-significant differences. This observation aligns with the findings of Nguyen et al 98 , who compared the performances of the extreme gradient boosting model relative to two evolutionary algorithms: genetic algorithms and differential evolution, i.e., GA-XGB and DE-XGB. Their study revealed that these models also displayed similar results.…”
Section: Resultssupporting
confidence: 90%
“…It’s important to highlight that DE and GA exhibited strongly non-significant differences. This observation aligns with the findings of Nguyen et al 98 , who compared the performances of the extreme gradient boosting model relative to two evolutionary algorithms: genetic algorithms and differential evolution, i.e., GA-XGB and DE-XGB. Their study revealed that these models also displayed similar results.…”
Section: Resultssupporting
confidence: 90%
“…The ndings revealed that the model was satisfactory in anticipating the arrival time of the oods. Nguyen et al [30] developed hybrid models by using two deeplearning models with XGBoost to forecast hourly water levels. The study veri ed that hybrid XGBoost models might be bene cial to many existing models for hourly water level prediction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research using machine learning techniques has gained popularity in flood prediction and monitoring. In some cases, machine learning approaches such as XGBoost [ 5 , 10 , 11 ], a tree-based supervised algorithm, have been used, as have KNN (K-Nearest Neighbours) [ 12 , 13 ]. The support vector machine (SVM) is commonly used in flood prediction models [ 14 ], and random forest and boosted tree models [ 15 , 16 ] have been used to assess flood susceptibility in recent years.…”
Section: Introductionmentioning
confidence: 99%